2008 38th European Microwave Conference 2008
DOI: 10.1109/eumc.2008.4751445
|View full text |Cite
|
Sign up to set email alerts
|

A 8W High efficiency X-band Power pHEMT amplifier

Abstract: A monolithic two-stage high power, high efficiency and high robustness amplifier was developed for X-band applications. The combination of the improvement of the UMS Power PHEMT technology called PPH25X in term of breakdown, and the adapted design regarding output mismatch and overdrive explain the performances of this device. The MMIC HPA, with a surface of 14.6 mm 2 , provides 8W output power in pulsed mode associated to a PAE of about 45 % at ambient temperature and can operate at 6dB compression in a wide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…AlGaN/GaN technology-based power amplifier biased at 20V for the X band application provided an output power between 21W to 28.5W for the frequency range from 8-10.5 GHz . The peak performance of this amplifier design provided an output power of 30W for the frequency ranging 8.5-9GHz [6,9]. A 10W power amplifier achieved an output power level of 42.03dBm at 2.4GHz [9].…”
Section: Related Workmentioning
confidence: 96%
“…AlGaN/GaN technology-based power amplifier biased at 20V for the X band application provided an output power between 21W to 28.5W for the frequency range from 8-10.5 GHz . The peak performance of this amplifier design provided an output power of 30W for the frequency ranging 8.5-9GHz [6,9]. A 10W power amplifier achieved an output power level of 42.03dBm at 2.4GHz [9].…”
Section: Related Workmentioning
confidence: 96%
“…Gallium Arsenide (GaAs) and Gallium Nitride (GaN) are competing for the future power devices and microwave applications, however due to material properties GaN based devices have more abilities to operate at high temperatures and high voltages than GaAs. Huet et al [3], presented the design of GaAs pHEMT power amplifier providing the maximum power added efficiency (PAE) of 45% operating over a bandwidth from 8-12 GHz. Chu et al [4] demonstrated the peak output power of 12.6W with peak PAE 52.6% at 9.4 GHz.…”
Section: A Prior Workmentioning
confidence: 99%
“…Recently, several HPAs have been fabricated on different substrates such as silicon [1,2], GaAs [3][4][5][6][7][8][9][10][11][12][13][14] and GaN [15][16][17][18]. GaN technologies have superior performance in power applications due to high breakdown voltage of the transistors, which results in high output power density.…”
Section: Introductionmentioning
confidence: 99%
“…A number of GaAs HPAs have been reported in the X and Ku frequency bands. For instance, 8-10 W HPAs are reported in [4][5][6][7][10][11][12][13]; however, all of the HPAs are narrowband designs. Hek has introduced a wideband PA in pulse mode regime [9], however the performance is degraded in continuous-wave (CW) mode.…”
Section: Introductionmentioning
confidence: 99%